“When I Think of Black Girls, I Think of Opportunities”: Black Girls' Identity Development and the Protective Role of Parental Socialization in Educational Settings - Burnett, Marketa; McBride, Margarett; Green, McKenzie N.; Cooper, Shauna M. (Frontiers in Psychology, 2022)
While educational settings may be envisioned as safe spaces that facilitate learning, foster creativity, and promote healthy development for youth, research has found that this is not always true for Black girls. Their negative experiences within educational settings are both gendered and racialized, often communicating broader societal perceptions of Black girls that ultimately shape their identity development. Utilizing semi-structured interviews with adolescent Black girls (n=12), the current investigation explored Black girls' educational experiences, their meaning making of Black girlhood, and the role of parents in their positive development. By centering Black girls’ voices, this study illuminated how Black girls negotiate their multiple marginalized identities and how their identities are shaped by their home and school environments. Findings revealed that Black girls are aware of the difficulties in navigating educational settings for Black girls, but this awareness was coupled with parental support that promoted positive gendered racial identities for Black girls in middle school and high school. This investigation advanced current knowledge of Black girls’ identity development and highlighted the protective role of parental socialization. Future research directions and implications are also discussed.